Интенсификация высказывания как проявление русского коммуникативного стиля - Лихачева, Алла Борисовна Борисовна (Slavistica Vilnensis, 2012)
Интенсивность является одной из активно дискутируемых категорий современной науки о языке, что можно объяснить повышенным вниманием лингвистов к проявлениям речевых интенций говорящего, а также качествами самих текстов, в том числе медиатекстов, все большей их экспрессивности и стилистической изощренности [см., напр., Шаховский 2011; Язык средств массовой информации 2008]. В русской лингвистике интенсивность понимается неоднозначно: как одно из средств усиления воздействующей силы языковой единицы [Шейгал 1981, 8], как ситуативно обусловленная яркость слова [Шаховский 2012], как мера количества экспрессивности [Туранский 1990, 21]. В свою очередь, экспрессивность считается составной частью более широкой категории выразительности, которая определяется “как совокупность таких качеств речи, которые обеспечивают ее полноценное восприятие адресатом, то есть восприятие, максимально приближенное к адекватному интенции автора пониманию и переживанию передаваемой информации” [Сковородников, Копнина 2008, 521]....Alla LikhachiovaIntensification of Utterance as a Manifestation of the Russian Communicative StyleThe article is devoted to the analysis of Russian intensifiers – words which provide the strong expressivity of Russian speech and texts. The category of intensity is defined as a measure of emotionality and expressiveness and a particular manifestation of the category of quantity (or graduality) in speech.For an adequate understanding of Russian texts, including media texts, not only explicitly expressed intensifiers, but also the implicit senses of intensifying words should be taken into account.In the article, attention is paid to the potential correlation between the intenseness of a text and the typical features of the Russian communicative style, such as emotional pressure, short psychological distance, retraction of the interlocutor into the speaker’s emotional sphere, etc.It is suggested that, for a proper understanding of the relation between the national mentality and the usage and popularity of certain lexical units, and, moreover, for an understanding of which languages are close to or far from Russian in speech intensity, the description of the level of linguistic expressiveness of the utterance in Russian, as well as in other languages, should include the research of a national communicative style.Keywords: Russian speech, intensifiers, expressivity, implicit senses, communicative style.